2007
DOI: 10.2106/jbjs.g.00567
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up on Misrepresentation of Research Activity by Orthopaedic Residency Applicants

Abstract: The prevalence of misrepresented research publications from orthopaedic surgery residency applicants increased modestly to 20.6% compared with that found in our original report (18%). As we recommended in our last report, we strongly urge residency programs to require applicants to submit reprints of their publications with their residency applications. Perhaps standardized guidelines should be developed to help to prevent misrepresentation through the Electronic Residency Application Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 18 publications
3
39
1
Order By: Relevance
“…Our study looked at 1975 publications submitted by 804 applications, and is to our knowledge, the largest study of this type during the longest span of time. A higher percentage of our plastic surgery applicants reported publications (79%) compared with other candidates in general surgery (31%), 10 neurologic surgery (71.6%), 5 orthopedics Phantoms by Plastic Surgery Residency Applicants (30%), 9,16 gastroenterology (58.5%), 14 dermatology (64%), 3 pediatrics (36.4%), 2 radiology (19.3%), 1,12,15 psychiatry (9.2%), 4 emergency medicine (32.3%), 7,8,13 and plastic surgery (73%). 11 Our definition of a phantom publication was an unverified citation or a verified citation not listing the applicant as an author.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our study looked at 1975 publications submitted by 804 applications, and is to our knowledge, the largest study of this type during the longest span of time. A higher percentage of our plastic surgery applicants reported publications (79%) compared with other candidates in general surgery (31%), 10 neurologic surgery (71.6%), 5 orthopedics Phantoms by Plastic Surgery Residency Applicants (30%), 9,16 gastroenterology (58.5%), 14 dermatology (64%), 3 pediatrics (36.4%), 2 radiology (19.3%), 1,12,15 psychiatry (9.2%), 4 emergency medicine (32.3%), 7,8,13 and plastic surgery (73%). 11 Our definition of a phantom publication was an unverified citation or a verified citation not listing the applicant as an author.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In particular, Larson et al have shown in plastic surgery that 3% of all citations submitted were misrepresented. 11 The purpose of our study is to determine the incidence of missing or "phantom" publications in plastic surgery residency applicants at a single institution over several application cycles.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Many publication misrepresentations are minor inaccuracies that do not affect the standing of the applicant. However, some misrepresentations are inaccuracies that are favorable to the applicant (such as advancing in the order of authorship) and some are clearly fraudulent (falsely claiming authorship of a verified publication and/or falsely claiming authorship of a nonexistent publication in a verified journal).…”
mentioning
confidence: 99%
“…Research activity is an important parameter of career performance in orthopedic surgery [6] and in other medical fields [7,8]. Yet, the prospect of authorship did not translate into a higher 6-week response rate in our survey.…”
mentioning
confidence: 74%